1998
DOI: 10.1093/humrep/13.7.1952
|View full text |Cite
|
Sign up to set email alerts
|

Novel vaginal danazol ring therapy for pelvic endometriosis, in particular deeply infiltrating endometriosis

Abstract: Danazol is routinely administered orally to inhibit ovulation and to treat pelvic endometriosis. However, recent evidence suggests that danazol can act directly on endometriotic tissue in vitro to inhibit DNA synthesis and induce apoptosis. Danazol was administered via the vagina in this study, using a vaginal ring drug delivery system containing 1500 mg of danazol. This therapy was effective for treatment of pelvic endometriosis, especially for deeply infiltrating endometriosis, resulting in a cure of dysmeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…This is probably due to the negligible systemic absorption leading to undetectable serum levels, as previously demonstrated (6). The low dose of danazol does not affect the pituitary ovarian axis and does not modify the endometrial thickness induced by estrogens and progesterone.…”
Section: Figuresupporting
confidence: 56%
See 1 more Smart Citation
“…This is probably due to the negligible systemic absorption leading to undetectable serum levels, as previously demonstrated (6). The low dose of danazol does not affect the pituitary ovarian axis and does not modify the endometrial thickness induced by estrogens and progesterone.…”
Section: Figuresupporting
confidence: 56%
“…A danazol-loaded vaginal ring has been tested with encouraging results in patients with deeply infiltrating endometriosis (6), and pain relief has been reported after use of a danazol-loaded intrauterine device in women with endometriosis (7). In addition, reduced side effects and proved safety suggest that the levonorgestrelreleasing intrauterine device may play an important role in long-term treatment of pain associated with endometriosis of the rectovaginal septum in patients with no immediate desire for pregnancy (8).…”
mentioning
confidence: 99%
“…Despite this, danazol is routinely administered orally. Igarashi et al (1998) successfully used a vaginal ring containing danazol to cure pelvic endometriosis and demonstrated that danazol is absorbed through the vaginal mucosa and reaches the deeply infiltrating endometriosis via diffusion. Adopting this principle in skin penetration, danazol provides a higher potency as an effective skin-whitening agent and thus it is desirable to study if danazol would demonstrate depigmenting activity at a clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…When endometriotic patients are administered danazol at 200-800 mg/day, endometrial atrophy occurs (9). However, local administration of low-dose danazol via vaginal danazol suppositories (13)(14)(15)(16), cervical injections of danazol suspensions (17) or use of intrauterine danazol rings (13,(18)(19) can improve endometriotic signs and symptoms without causing any menstrual disorders. Local danazol therapy does not inhibit either endogenous estrogen production or ovulation, in contrast to the effects of oral danazol therapy (13,14,16).…”
Section: Introductionmentioning
confidence: 99%